Are Speedy Brains Needed when Divergent Thinking is Speeded—or Unspeeded?. (7th May 2018) - Forthmann, Boris; Lips, Corinna; Szardenings, Carsten; Scharfen, Jana; Holling, Heinz
Abstract: In this study, we focus on mental speed and divergent thinking, examining their relationship and the influence of task speededness. Participants ( N = 109) completed a set of processing speed tasks and a test battery measuring divergent thinking. We used two speeded divergent‐thinking tasks of 2 minutes and two unspeeded tasks of 8 minutes to test the influence of task speededness on creative quality and their relation to mental speed. Before each task, participants were instructed to be creative in order to optimally measure creative quality. We found a large main effect of task speededness: less creative ideas were generated when tasks were speeded as compared to unspeeded (Cohen's d = −1.64). We could also replicate a positive relationship of mental speed with speeded divergent thinking ( r = .21) and mental speed with unspeeded divergent thinking ( r = .25). Our hypothesis that the relation is higher for the speeded divergent‐thinking tasks was not confirmed. Importantly, variation in creative quality scores under speeded conditions was not explained by mental speed beyond the predictive power of unspeeded creative quality. The latter finding implies that measurement of creative quality under speeded conditions is not confounded by mental speed.